Development of Interactive Multimedia Based on Website to Get to Know Indonesia as One in Diversity in Grade IV - Wiguna, Frans Aditia; Yuliyanti , Diah Kurnia (JURNAL PENDIDIKAN DASAR NUSANTARA, 2025)
This website-based interactive multimedia development research aims to attract students' attention, make students more active in the learning process, and help students understand the material, meet students' learning styles by creating a pleasant learning atmosphere, encourage students to understand the material on Indonesian diversity, develop student character according to the profile of Pancasila students, and provide media that is appropriate for the age of students in the concrete operational stage. The validation of website-based pop-up book visual multimedia carried out by the media validator obtained results with a percentage of 82% with a very valid category, the results of the material validation were 92% which means that the material used in the website-based pop-up book visual multimedia developed was very valid. Based on the average results of the student response questionnaire, the results were 91% and stated to be very practical, the minimum learning completion criteria were > 75, so website-based interactive multimedia can be said to be effective in improving student learning outcomes. The type of research used was research and development. The development stages used used the ADDIE model stages (Analysis, Design, Development and Implementation). The effectiveness results show that student evaluation results increased from 61% to 85% of students achieving the KKM score.